2017
DOI: 10.1177/0971721817723383
|View full text |Cite
|
Sign up to set email alerts
|

Role of Information in SMEs Supporting Services on Business Performance in South Korea

Abstract: Role of InfoRmatIon In SmeS SuppoRtIng SeRvIceS  441 were analysed to investigate the relationship between two variables such as independent variables versus mediating variables, independent variables versus dependent variables and mediating variables versus dependent variables. The route from information provision in SME supporting services to business performances was clarified by using Baron and Kenny's mediation model. 'information overload occurs when the amount of input to a system exceeds its processin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
2
4
0
Order By: Relevance
“…Therefore, it can be seen that it is important to consider mediating factors when analysing the SME business performances by SME supporting services. This result is consistent with our previous study (Park et al, 2017).…”
Section: Resultssupporting
confidence: 95%
See 2 more Smart Citations
“…Therefore, it can be seen that it is important to consider mediating factors when analysing the SME business performances by SME supporting services. This result is consistent with our previous study (Park et al, 2017).…”
Section: Resultssupporting
confidence: 95%
“…Therefore, it can be seen that it is important to consider mediating factors when analysing the SME business performances by SME supporting services. This result is consistent with our previous study (Park et al, 2017). Moderating effect of technology and market dynamism on SME performances was analysed when the independent variable was the contribution degree to decision-making.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…It is not possible to absorb knowledge from the outside if one cannot even create or store internal knowledge in a way that it can benefit the whole organization. It was also showed that small and medium enterprises are more prone to develop open innovation due to being more flexible [41,44].…”
Section: Discussion: Open Innovation In Knowledge Management Maturitymentioning
confidence: 99%
“…The growth of companies is measured using growth rates of several factors such as sales, employment, assets, capital, and profits [43,[48][49][50][51][52][53][54]. Especially, sales and employment reflect both the short-term and long-term changes of companies and can be a more objective measure of growth [43,55,56]. The relative growth is usually measured as a percentage growth rate [42,57], and this study uses both absolute and relative growth measures.…”
Section: Measurement Of Variablesmentioning
confidence: 99%